Role of caregivers on medication adherence management in polymedicated patients with Alzheimer's disease or other types of dementia - Muñoz-Contreras, María Cristina; Segarra, Ignacio; López-Román, Francisco Javier; Galera, Raúl Nieto; Cerdá, Begoña (Frontiers in Public Health, 2022)
Background: Alzheimer disease (AD) and other dementia patients may have severe difficulties to ensure medication adherence due to their generally advanced age, polymedicated and multi-pathological situations as well as certain degree of cognitive impairment. Thus, the role of patient caregivers becomes crucial to warrantee treatment compliance. Purpose: To assess the factors associated to patients and caregivers on medication adherence of patients with AD and other types of dementia as well as the degree of caregiver satisfaction with respect to treatment. Methods: An observational, descriptive, cross-sectional study among the caregivers of 100 patients with AD and other types of dementia of the ‘Cartagena and Region Association of Relatives of Patients with Alzheimer's Disease and other Neurodegenerative Diseases’ was conducted to assess patient and caregiver factors that influence medication adherence evaluated with the Morisky-Green test. Results: Overall adherence to treatment was 71% with similar proportions between male and female patients. Greater adherence was found in married or widowed patients (49.3%), a first degree (85.9%) or female (81.7%) caregivers and lower in AD patients (75.9%). Multivariate analysis showed a statistically significant positive association between non-adherence with the male sex of the caregiver (OR 3.512 [95%IC 1.124-10.973]), dementia (OR 3.065 [95%IC 1.019-9.219]), type of caregiver (non-first-degree relative) (OR 0.325 [95%IC 0.054-0.672]) and civil status of the patient (OR 2.011 [95%IC 1.155-3.501]) favorable for married or widowed patients. No or week association was found with gender, age, education level, number of drugs used or polymedicated status of the patient. Conclusions: Caregivers influence therapeutic management with predictors for improved adherence including female gender and first-degree kinship, together with patient’s marital status. Thus, training caregivers about the disease and the importance of medication adherence in AD patients may ensure optimal treatment.